Coagulation testing in the evaluation of suspected child abuse - Olivieri, M.; Kurnik, K.; Bidlingmaier, C. (Hämostaseologie, 2009)
Every year in Germany nearly 3000 cases of child abuse were reported. When children are presented at emergency units with suspicious injuries and bruises a detailed documentation an evaluation is necessary after emergency treatment. As differential diagnosis inherited or acquired bleeding disorders should be excluded. In addition to a detailed evaluation of personal and family history and a physical evaluation different coagulation test to exclude defects of primary and secondary hemostasis should be performed. Clinician must know the limitations of these tests and keep in mind that an abnormal coagulation test does not exclude child abuse. Coagulation defects may be the consequence of child abuse and neglect or the two conditions may coexist.
Keywords: Child abuse; coagulation